Predominant mycobiota and aflatoxin content in Brazil nuts - Freitas-Silva, Otniel (2011)
Abstract The Brazil nut (Bertholletia excelsa) is an economically important product to the Brazilian Amazon. Currently, its marketing is being affected by the high incidence of aflatoxins (AF) produced by potentially aflatoxigenic fungi associated with its seeds. In this context, the purpose of this study was to determine which part of the nut contributes to contamination by aflatoxins and to identify the mycobiota in Brazil nut samples. Unshelled and shelled nuts were analyzed by measuring the total count of filamentous fungi (Aspergillus sections Flavi, Nigri and Circumdati) in sanitised and non-sanitised treatments. The isolates identified as Aspergillus section Flavi, the major producers of AF, were plated for determination of their aflatoxigenic potential. To perform the AF analysis, samples of Brazil nuts were treated separately. The AF from the shell and kernel were extracted by chloroform and analysed by the HPLC-FD system in isocratic mode. The Aspergillus section Flavi count was 21.67% lower. The production of AF by the isolated fungi was 30% for sanitised and 23.8% for non-sanitised samples. The concentrations obtained of AFB1 and AFG1 were higher than those of AFB2 and AFG2. The AFB1 concentrations of shelled nuts and shell samples were 35.0 and 1.78 lg/kg, respectively. AFB2 and AFG2 were detected only in shelled nut samples. The HPLC-FD analysis presented limits of detection (LOD) and quantification (LOQ) of 0.2 and 0.4 lg/kg, respectively.